2021
DOI: 10.3389/fpsyt.2021.633717
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition in Schizophrenia

Abstract: Deficits in facial emotion recognition are one of the most common cognitive impairments, and they have been extensively studied in various psychiatric disorders, especially in schizophrenia. However, there is still a lack of conclusive evidence about the factors associated with schizophrenia and impairment at each stage of the disease, which poses a challenge to the clinical management of patients. Based on this, we summarize facial emotion cognition among patients with schizophrenia, introduce the internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 63 publications
1
28
1
Order By: Relevance
“…Facial expression is also a good vehicle of emotional signals [44,45]. Since part of the face is covered with the VR goggles, the inference of emotion has to be made through mouth and lips shape [46,47].…”
Section: Data Integration and Processingmentioning
confidence: 99%
“…Facial expression is also a good vehicle of emotional signals [44,45]. Since part of the face is covered with the VR goggles, the inference of emotion has to be made through mouth and lips shape [46,47].…”
Section: Data Integration and Processingmentioning
confidence: 99%
“…This automatic processing is largely attributed to the emotional salience portrayed by a face, whereby expressions of anger, fear and disgust significantly raise our vigilance and give an evolutionary advantage for avoiding harm (Murphy and Zajonc, 1993 ; Öhman, 2002 ). By contrast, difficulties with face perception may severely impact social cognitions, e.g., emotion recognition and interpretation of social cues, as seen in autism spectrum disorders and schizophrenia (Kleinhans et al, 2011 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one of the most researched social cognitions in schizophrenia is facial emotion recognition (FER). Unfortunately, FER was found to be impaired in patients with schizophrenia 5,6 . Another study showed that de ciency in FER were stable across phases of schizophrenia and were already present in rst-episode schizophrenia (FSZ) patients 7 .…”
Section: Introductionmentioning
confidence: 99%